Pressure Reduction Effects of Compressible Materials on the Buried Pipes Subjected to Large Surcharges - Marcin Kochanowicz; Vo Van Hoang (Advances in Engineering and Intelligence Systems)
Compressible materials including Expanded Polystyrene (EPS) blocks have been extensively used in many geotechnical applications to reduce the effects of applied pressure. Of particular concern where a high embankment is placed above a buried pipe, excessive deformation and stresses may be developed in the pipe walls. The induced Trench Installation (ITI) method could be used as an alternative to mitigate the transferred pressure to the buried structure. In this method, a compressible zone is installed above the buried pipe to induce positive soil arching and subsequently reduce applied pressure to the pipe. This study aims to investigate the efficiency of the various configuration of EPS geofoam (as compressible material) on the performance of the buried pipe subjected to a large surcharge. Two-dimensional numerical analyses were conducted considering the incrementally increasing pressure applied on the surface of dry sand containing buried pipe. The analysis results were compared to the no EPS state to present the effectiveness of different EPS arrangements. It was concluded that the stiffness of geofoam blocks significantly affects the mechanical response of buried structure. Furthermore, applying compressible materials with a specific array leads to the development of excessive axial force and bending moment in the pipe wall and has adverse effects on the pipe performance.